Clorinda Matto de Turner in Buenos Aires: an unpublished letter to Robert Lehmann-Nitsche (02/01st /1906) - Matienzo León, Ena Mercedes (2016)
The following paper is intended to reveal a letter that Peruvian writer Clorinda Matto de Turner addressedfrom Buenos Aires, in 1906, to physical anthropologist and ethnologist Robert Lehmann-Nitsche. The letterthat is written by hand, and it is visible the Cusco poligrapher’s signature, is preserved in the library of the Ibero-American Institute in Berlin, in the section of legacies, autographs, drawings and other photographicdocumentations. This brief study is a first research on a wide recorded correspondence that possibly Matto de Turner addressed to some academic, political and religious personalities. The publication of this first letter offers information on the spaces in which the Peruvian writer move at the beginning of the 20th century.